Role of Engineering in Controlling Sediment into Reservoirs - Murthy, B.N. (Journal of Soil and Water Conservation, 2022)
It has been realised that uncontrolled deforestation, forest fires, over. grazing, improper methods of tillage and unwise agricultural practices have acclerated soil erosion resulting in a considerable increase of sediment flow in streams.To meet the vagaries of nature and to serve the community, storage reservoirs are inevi-table. Whenever we think of storage reservoirs, we have to immediately think of its attending evil, silting. A reservoir is an artificial lake and it begins to fill with sediment the moment it is formed and gradually dies from loss of its capacity caused by the deposition of sediment brought by the inflowing water. Most of our modern reservoir dams are engineered to have a practically unlimited life so far the structure itself is concerned, provided it is given a reasonable maintenance. 'Rivers are the mortal enemies of lakes'. Thus, it is seen that though most of the dams are constructed to last almost indefinitely, they will become largely useless from silting, long before the dams themselves reach a stage of significant deterioration.